Efektivitas Media Board Game Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Theana Putri Permananda; Wahyudi (LPPM Universitas Buana Perjungan Karawang, 2020)
The purpose of this research is to figure out the effectiveness toward problem solving skill in thematic course by using Board Game as the medium of Teams Games Tournament learning discourse. Pre experimental design which applies in this research is using one group pretest - post test pattern. The collecting data done by using test, observation, and interview. The effectiveness by using Board Game can be seen in the result of pretest and posttest about problem solving skill by Paired Sample testing and assisted with SPSS 25.0 for windows program. Paired T-Test result obtained from Sig score. (2-tailed) same to 0,000 or less than 0,05 with the pretest average 65% and 79% for the post test. Furthermore, Board Game is effective to enhance the problem solving skill